Utilising community pharmacists to reduce prescribing waste. Issue 3 (30th March 2018) - Brown, Richard
Abstract : Community pharmacy teams are in a unique position to identify opportunities for medicines optimisation. Richard Brown describes a joint project carried out between Avon Local Pharmaceutical Committee and Bath and North East Somerset CCG that utilised community pharmacists to identify and reduce prescribing waste.